Socio-cultural Aspects of Federal Structure in Nepal - Yadav, Shiva Kumar (Academic View, Journal of TUTA Tri-Chandra Campus Unit, 2023)
The decade long maoist insurgency and the joint effort of the existing seven political parties’ alliance like Nepali Congress, CPN UML and others overthrew the monarchy transforming the country into republic state deciding to adopt federal system of governance. The sole motto of federal notion as said is the equitable justice, accommodation of diversities and wholesome development regarding the economic, socio-cultural, political and international prospects. Before unification of Nepal, It was divided into a numerous principalities and kingdoms, with its own system of governance following the social and cultural autonomy, the own mode of production. The political front formed then after slowly and consistently came under centralized form of administration, annihilation of the local systems slowly. The local systems, usages, local identity, local aspirations, social and cultural diversity were encroached and suppressed in systematic manner. The state unites physically but the rational cultural, social unification left behind by the contemporary ruler and governance that invites for the socio-cultural federalization.